Recreaciones del Inca Garcilaso en la narrativa peruana: la guerra de las Alpujarras a través de la perspectiva identitaria - Rodríguez Mansilla, Fernando (2024)
Narrative recreations about the life of Inca Garcilaso are full of anachronistic elements, for they are current interpretations of the past, which deal with the role of his figure in the Peruvian cultural imagination. This work analyzes the way in which contemporary Peruvian narrators have recreated Garcilaso’s participation in the war of Alpujarras. The recreation of this military episode in Garcilaso’s life and its impact on him unfolds a empathy towards the Moriscos as a matter of identity around the literary construction of Garcilaso as a character.